Boots on the Ground : Disaster Response in Canada - Botha, Johanu (Book collections on Project MUSE., 2022)
"Over the last century, the scale of Canada's domestic disaster response system has grown significantly due to the country's increased capacity for emergency management and the rise in natural hazards. However, there has been no systematic assessment of how effectively this multilevel system, which includes all levels of government and the military, has been integrated, and how efficient this system actually is at responding to high-level disasters. Using in-depth archival analysis and interviews with senior military and civilian officials on the inside, Boots on the Ground provides a detailed examination of Canada's disaster response system. Including policy recommendations focused on the expansion of emergency management networks, the maintenance of Canada's decentralized emergency management system, and disaster response resources for First Nations communities, Boots on the Ground aims to highlight opportunities to improve Canada's urgent disaster response. Boots on the Ground offers helpful lessons for students, policy makers, emergency management practitioners, and military officers, ensuring that readers gain concrete insights into the strategic and efficient implementation of disaster response initiatives."--